PENGARUH KUALITAS PRODUK, HARGA, DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN - Rukmayanti Rukmayanti; Fitriana Fitriana (Universitas Ahmad Dahlan, 2022)
The purpose of this study is to determine the effect of product quality, price, and promotion on purchasing decisions for MS Glow product. This study used primary data with a number of samples of 100 respondents. Data analysis methods used include validity tests, reliability tests, multiple linear regression analyses, and hypothesis testing. The results of the data analysis indicate that product quality have a positive effect on purchasing decisions, promotion have a positive effect on purchasing decisions, and price have a negative but no significant effect on purchasing decisions.